Determinants of Educated Unemployment in Indonesia: A Comprehensive Logistic Regression Analysis - Wafi, Faiz Abdullah; Kafa, Muhammad Zidny (Convergence: The Journal of Economic Development, 2024)
Abstract Indonesia faces a fairly serious problem of educated unemployment amid the potential for a demographic dividend. In 2021, the educated unemployment rate reached a percentage of 8.55%, representing an increase of 1.86% compared to the previous year. Using logistic regression estimates, this study aims to examine the characteristics underlying the phenomenon of educated unemployment in Indonesia. The data used in this study were sourced from the 2022 National Labor Force Survey (Sakernas) conducted by the Indonesian Bureau of Statistics (BPS). The findings reveal that gender, marital status, household status, and migration significantly influence the likelihood of being part of the educated unemployed. Specifically, highly educated female workers are 1.9 times more likely to be unemployed compared to their male counterparts. This study highlights the persistence of gender disparities in Indonesia's labor market, even when women possess educational qualifications equivalent to men. Furthermore, this study has important implications for public policy and the Indonesian labor market. First, findings on the gender gap point to the need for policies that support equality in access to work, especially for women with higher education. Second, the influence of household status and migration indicates the need for more flexible skills training and workforce mobility programs. Third, these results can be the basis for the government in formulating education policies that are more in line with the needs of the job market. Overall, this study provides insights to reduce educated unemployment and make optimal use of the potential demographic bonus. Keywords:Educated Unemployment, Gender, Marital Status, Household Status, Migration Abstrak Indonesia menghadapi masalah pengangguran terdidik yang cukup serius di tengah potensi bonus demografi. Pada tahun 2021, tingkat pengangguran terdidik mencapai persentase 8,55%, yang merupakan peningkatan sebesar 1,86% dibandingkan dengan tahun sebelumnya. Dengan menggunakan estimasi regresi logistik, penelitian ini bertujuan untuk mengkaji karakteristik yang mendasari fenomena pengangguran terdidik di Indonesia. Data yang digunakan dalam penelitian ini bersumber dari Survei Angkatan Kerja Nasional (Sakernas) 2022 yang dilakukan oleh Badan Pusat Statistik (BPS) Indonesia. Hasil penelitian ini menunjukkan bahwa jenis kelamin, status pernikahan, status rumah tangga, dan migrasi secara signifikan mempengaruhi kemungkinan menjadi bagian dari pengangguran terdidik. Secara khusus, pekerja wanita dengan tingkat pendidikan tinggi memiliki memiliki peluang menganggur lebih tinggi sebesar 1,9 kali dibandingkan laki-laki. Penelitian ini menyoroti keberlanjutan kesenjangan gender di pasar tenaga kerja Indonesia, meskipun perempuan memiliki kualifikasi pendidikan yang setara dengan laki-laki. Selanjutnya, penelitian ini memiliki implikasi penting untuk kebijakan publik dan pasar tenaga kerja Indonesia. Pertama, temuan mengenai kesenjangan gender menunjukkan perlunya kebijakan yang mendukung kesetaraan dalam akses pekerjaan, khususnya bagi perempuan dengan pendidikan tinggi. Kedua, pengaruh status rumah tangga dan migrasi mengindikasikan perlunya program pelatihan keterampilan dan mobilitas tenaga kerja yang lebih fleksibel. Ketiga, hasil ini dapat menjadi dasar bagi pemerintah dalam merumuskan kebijakan pendidikan yang lebih sesuai dengan kebutuhan pasar kerja. Secara keseluruhan, penelitian ini memberikan wawasan untuk mengurangi pengangguran terdidik dan memanfaatkan potensi bonus demografi secara optimal.  Kata kunci:Pengangguran Terdidik, Gender, Status Pernikahan, Status Rumah Tangga, Migrasi